Abraham Lincoln, slavery, and the Civil War : Selected writings and speeches - Johnson, Michael P. (The Bedford series in history and culture, 2011)
Incorporating famous documents and crucial letters, Abraham Lincoln, Slavery, and the Civil War walks you through the development where Lincoln stood on all the critical issues of the day, including free labor, antebellum politics and the Republican party, slavery, secession, the Civil War, and emancipation.